Health in Nepalese Media - Mishra A, Joshi P, Kumal AB, Ghimire J (Journal of Nepal Health Research Council, 2013)
Background: Coverage of health in Nepali print media is quite a recent phenomenon despite readers’ ample appetite for it. Dominated by politics, Nepal’s print media has been marginally publishing news pieces, features, editorials and op-ed articles, photographs and cartoons on health, though marginally. But the media did not wake up to the issues of human resources for health until lately. Methods: We content analysed the coverage of health issues including, human resources for health in select Nepali print media Kantipur, Nagarik and Annapurna Post of select three months in 2012 April, August and December. News pieces and their placements, Op-eds, editorials, features, letters to the editor, photos and cartoons were subjected to analysis. Results: Over the study period, the papers covered 544 health news pieces, 44% of political news pieces. Health workforce news pieces contributed 24% to it. However, only 10% of the health news made to the front pages. Coverage of health in editorials, features, Op-eds, photographs, cartoons and letters to the editor is even more meager. For example, only 7% of the editorials are relating to health. Conclusions: Health is prioritized far less by the print media than politics despite the reader’s appetite for it. Print media should give health a top priority, particularly in those areas that relate to health systems like human resources for health, for their massive impact on the lives of the people.